Exploring Consumer Behaviour towards Zero- Sugar Beverages: A Case Study of Delhi NCR - Amit Kumar Gond,; Balu Shagila Sai Raswanth,; Surliya, Vikash; Satyveer Singh Meena, (Indian Journal of Extension Education, 2025)
In recent years, rising consumer health consciousness has led to a significant shift in beverage consumption patterns, especially in urban areas like Delhi National Capital Region (NCR). This research aims to understand consumer behaviour towards zero-sugar beverages in the Delhi NCR. A structured survey of 320 respondents across different age groups, income levels, and health profiles was conducted using a structured questionnaire in 2025 through multistage sampling. Factor analysis was employed as a statistical tool to analyze consumer behaviour and perception towards zero-sugar beverages. A chi-square test was used to examine the relationship between customers' awareness of zero-sugar beverages and their level of education. In the findings, two significant factors had arisen: one concerned consumers influenced by health fears and mistrust; the other was health-conscious or positive consumers, motivated by fitness, health, and informed choices. According to the study, respondents who were highly concerned about their health and concerned about labels preferred sugar-free beverages. There was considerable dissent about the deception that sugar-free beverages are solely for persons with diabetes. The study's overall conclusions indicate that the sugar-free beverage industry in Delhi NCR is still relatively nascent but has a lot of potential.